Enhancing Pedagogical Content Knowledge in Mathematics Teachers Through Collaborative Professional Development - Maudia, Nelva; Awodeyi, Amos Folayan; Mohammed, Abubakar Siddiq (Interval: Indonesian Journal of Mathematical Education, 2024)
Purpose of the study: The purpose of this study is to explore how collaborative professional development programs can enhance the Pedagogical Content Knowledge (PCK) of mathematics teachers, particularly in integrating pedagogy with content, improving teaching strategies, and addressing challenges in the classroom. Methodology: This study uses a qualitative research design with a case study approach. Data collection tools include in-depth interviews, classroom observations, and document analysis. The participants consist of 20 middle school mathematics teachers. Data analysis is conducted using thematic analysis, with a focus on identifying patterns and themes related to the development of PCK. Main Findings: The study found that collaborative professional development significantly improved teachers' ability to integrate pedagogy with content, implement innovative teaching strategies, and develop more structured lesson plans. Additionally, 75% of teachers reported increased student engagement, while 60% faced challenges related to time and resource limitations. Novelty/Originality of this study: This study provides new insights into the effectiveness of collaborative professional development in enhancing Pedagogical Content Knowledge (PCK) among mathematics teachers. It contributes to existing knowledge by demonstrating the impact of collaborative learning on teaching strategies and identifies key challenges, offering valuable implications for future teacher training programs.